Profitability of Clove Leaf Oil Agroindustry Business In Gantarang District, Bulukumba Regency, South Sulawesi - A. Muhammad Reski; Sri Mardiyati; Muh Ikmal Saleh; Mohammad Natsir (International Journal of Business and Quality Research, 2025)
Cloves are a plantation commodity that has multiple functions, ranging from health, beauty, industry, cooking spices, and so on. This study aims to determine the income and feasibility of the clove leaf oil agroindustry in Benteng Gantarang Village, Gantarang District, Bulukumba Regency. The sampling technique in this study used purposive sampling technique, namely the owner of the clove leaf oil distillation business. The sample of clove leaf oil entrepreneurs was obtained from 5 home industries. The types of data include primary data and secondary data. Data analysis used quantitative descriptive analysis. The results of this study indicate that the clove leaf oil agroindustry business in Benteng Village, Gantarang District, Bulukumba Regency has an average production of 240 liters per month, with a price of Rp 200,000.00 per liter, the revenue is Rp 48,000,000.00, while the total cost reaches Rp 7,226,951.49 so that the income of this business is Rp 40,773,048.51 per month. The clove leaf oil agroindustry business in this village has an average R/C ratio of 6.62, making it very profitable. This means that for every one rupiah of costs incurred for the clove leaf oil agro-industry business, the revenue obtained reaches Rp 6.62. Thus, the clove leaf oil agroindustry business is very feasible to be developed because it is very profitable.